Implementation students’ speaking skills by using #duet English conversation on TikTok at SMAN 5 Padang - Putra, Jasrike; Ayudhia, Honesty Yonanda (Journal of English Language Teaching, 2025)
This study used pre-experimental that is aimed to found out the improvement of students’ speaking skill by using #duet english conversation on Tiktok. The research population was students of eleventh grade at SMAN 5 Padang. To select one class as the sample, this study used The Cluster Sampling. To Collect the data, this study used #duet english conversation on Tiktok in the treatment and speaking test. The findings of the research conclude that using #duetenglishconversation effectively enhances and improves speaking skills. The results of the pre-test and post-test has significance differences confirms that using #duet english conversation on tiktok develops students’ speaking skill in english communication.